Assessment of Wheat Farmers’ Knowledge through Kisan Call Centre Advisory Services in Prayagraj, India - Rahul Kumar; Kumar Sonu; Syed H Mazhar; Ajay Verma; Vaibhav Singh (Indian Journal of Extension Education, 2026)
The study examined the effectiveness of Kisan Call Centre (KCC) as an ICT-enabled extension tool in disseminating improved wheat cultivation knowledge among Prayagraj district’s farmers, during 2023-24. A purposive sampling design was employed to select 120 wheat farmers from Chaka block who had utilized KCC services. Data were collected through structured interviews and analysed using descriptive statistics, Chi-square test, and correlation analysis. Results revealed that while 93.49% of farmers were aware of KCC's existence, their knowledge of advanced extension services remained limited. Only 17.88% had a complete understanding of KCC objectives, and awareness about weather advisories (9.94%), conference call facilities (8.13%), and governing agencies (8.13%) was poor. Knowledge distribution showed 50.83% farmers in the medium category, 41.67% in the high category, and 7.50% in the low knowledge category. Chi-square analysis indicated a significant association between age and knowledge levels (χ² = 166.66, p